Emergency general surgery utilization and disparities during COVID-19: an interrupted time-series analysis. Issue 1 (18th March 2021) - Greenberg, Anya L; Schwartz, Hope; Collins, Caitlin R; Kelly, Yvonne M; Mackersie, Robert; Mourad, Michelle; Roberts, John P; Bongiovanni, Tasce
Abstract : Objective: We aimed to compare general surgery emergency (GSE) volume, demographics and disease severity before and during COVID-19. Background: Presentations to the emergency department (ED) for GSEs fell during the early COVID-19 pandemic. Barriers to accessing care may be heightened, especially for vulnerable populations, and patients delaying care raises public health concerns. Methods: We included adult patients with ED presentations for potential GSEs at a single quaternary-care hospital from January 2018 to August 2020. To compare GSE volumes in total and by subgroup, an interrupted time-series analysis was performed using the March shelter-in-place order as the start of the COVID-19 period. Bivariate analysis was used to compare demographics and disease severity. Results: 3255 patients (28/week) presented with potential GSEs before COVID-19, while 546 (23/week) presented during COVID-19. When shelter-in-place started, presentations fell by 8.7/week (31%) from the previous week (p<0.001), driven by decreases in peritonitis (β=−2.76, p=0.017) and gallbladder disease (β=−2.91, p=0.016). During COVID-19, patients were younger (54 vs 57, p=0.001), more often privately insured (44% vs 38%, p=0.044), and fewer required interpreters (12% vs 15%, p<0.001). Fewer patients presented with sepsis during the pandemic (15% vs 20%, p=0.009) and the average severity of illness decreased (p<0.001). Length of stay was shorter during the COVID-19 period (3.91 vs 5.50 days, p<0.001). Conclusions: GSE volumes and severity fell during the pandemic. Patients presenting during the pandemic were less likely to be elderly, publicly insured and have limited English proficiency, potentially exacerbating underlying health disparities and highlighting the need to improve care access for these patients. Level of evidence: III.